Quality assurance in primary total hip arthroplasty - Koutras, Christos (J Orthop, 2020)
OBJECTIVE: To compare two different methods of clinical outcomes documentation and investigate the potential impact of a quality assurance program. METHODS: Data on primary hip arthroplasties conducted between 2004 and 2014 were prospectively collected and analyzed. RESULTS: A total of 262/3395 patients suffered a postoperative complication. A reduction of complication rate was observed between 2010 and 2014. A significant difference between the two documentation methods was found in: “cardiovascular complications”, “hematoma and postoperative hemorrhage” and “reintervention”. Finally, the “normalized length of hospital stay” predicted the occurrence of complications. CONCLUSION: Reduction of the incidence of complications through time may be attributed to accumulated surgical experience.